The fishery and biology of Meretrix casta(Chemnitz) in the Moorad estuary, Kerala - Laxmilatha, P; Thomas, Sujitha; Sivadasan, M P; Ramachandran, N P; Surendranathan, V G (Indian Journal of Fisheries, 2011)
Meretrix casta forms an important fishery in the Moorad estuary. The averageannual landing for the period 2000-2004 was 426t, the average catch per effortwas 573 kg and total effort was 3182. Clams ranging from 28 to 32 mm sizecontributed to the fishery. M casta is a continuous breeder with two peaks inMarch-April and August-September. The precentage edibility ranged between8 and 16. The standing stock biomass in the Moorad estuary was estimated at2073 t with an average density of 1096 numbers per sq. m. The present statusand management options for this important fishery are discussed.